Arteries and veins: making a difference with zebrafish - Lawson, Nathan D.; Weinstein, Brant M. (Nature reviews. Genetics, 2002)
Key Points One of the most fundamental distinctions between blood vessels is that between arteries and veins. These two types of vessel are structurally different and have long been functionally defined by the direction of the flow of blood that they carry. Recent work indicates that the endothelial cells that line the lumens of these two vessel types have distinct molecular identities. Arterial–venous endothelial-cell identity is determined during embryogenesis, before circulation begins. Recent work in several vertebrates has begun to define the molecular pathways that specify this differentiated fate. The zebrafish has been particularly useful for in vivo dissection of the signalling pathways that regulate arterial and venous fate. Zebrafish provide several advantages for studying vascular development. They are amenable to large-scale forward genetics analysis. The optical clarity, external embryonic development and small size of zebrafish embryos also allow easy visualization of the vasculature and allow screening for vascular-specific mutants. Components of the Notch pathway are expressed in the blood vessels of many vertebrates, and several Notch receptors are expressed specifically in arterial endothelial cells. Studies in zebrafish have now shown that the activation of Notch signalling in endothelial cells promotes arterial cell fate and represses venous differentiation. Studies in the zebrafish have also shown that the well-known signalling molecules — sonic hedgehog and vascular endothelial growth factor (Vegf) — act upstream of Notch signalling to promote arterial differentiation of endothelial cells. Several recent studies in the mouse have confirmed that Vegf also has an important role in arterial specification in this organism. The powerful genetic tools provided by the zebrafish will allow both the identification of other molecules that are involved in arterial differentiation and the placement of these molecules in a genetic pathway. The conservation of signalling mechanisms and the similarity of embryonic and adult neovascularization indicate that the differentiation of arterial and venous endothelial cells will probably be relevant in the context of human disease. Arteries and veins are structurally different and have long been functionally defined by the direction of blood flow that they carry. However, a growing body of evidence indicates that the identity of the endothelial cells that line these vessels is determined in the developing embryo, before circulation begins. Recent work on the zebrafish has led to the identification of signals that are responsible for arterial and venous differentiation of endothelial cells, and highlights the unique benefits of this model organism in the study of vascular development.